A Causal Comparative Research; An Evaluation Of The Motivational Aspect Of Tell Me More (TMM) Language Learning Software From The First Year Low And High Proficiency Undergraduates Of Islamic University College Of Malaysia. - Suraini Mohd Ali,; Nur Muhammad Insan Jalil (Universiti Sains Islam Malaysia, 2024)
This research seeks to find out the differences between the low and high proficiency undergraduates of Islamic Science University College of Malaysia (KUIM) in terms of the motivational aspect in using Tell Me More (TMM) Language Learning Software. The respondents are 200 First Year Undergraduates from the low and high proficiency groups. A set of questionnaire - 'Instructional Material Motivation Survey' (IMMS) Instrument are administered on 200 undergraduates after they have used TMM for 8 weeks. The questionnaires are collected and analyzed using SPSS to arrive at statistical analysis. Analysis shows that there is not much disparity between the low and high proficiency learners in terms of their motivational level in using TMM software. It also illustrates that learners' proficiency level is not the only contributing factor in determining the motivational levels in the software usage. In addition, the analysis also delineates that TMM software is evaluated as moderately motivating software by the low and high proficiency undergraduates. The strengths and weaknesses in TMM pertaining to the features in the ARCS Model (Attention, Relevance, Confidence and Satisfaction) are also noted. The strengths are from the aspect of ATTENTION and RELEVANCE and the weaknesses are from the aspect of CONFIDENCE and SATISFACTION in using the software. The identified weaknesses are expected to be improved by implementing and practicing the recommendations presented in this research report.